2005
DOI: 10.1016/j.femsim.2004.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of anti-β-glucan antibody in host defense against fungi

Abstract: We have recently detected an anti-beta-glucan antibody in normal human and normal mouse sera. The anti-beta-glucan antibody showed reactivity to pathogenic fungal Aspergillus and Candida cell wall glucan. Anti-beta-glucan antibody could bind whole Candida cells. It also enhanced the candidacidal activity of macrophages in vitro. The anti-beta-glucan antibody titer of DBA/2 mice intravenously administered either Candida or Aspergillus solubilized cell wall beta-glucan decreased remarkably dependent on dose. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 44 publications
1
46
1
Order By: Relevance
“…4). Although detection of an anti-β-glucan antibody in normal human and mouse sera has been reported previously (17,27), we found, for the first time, the presence of anti-Sophy β-glucan IgG antibody in serum samples prepared from the umbilical cord blood of neonates. The mechanism(s) of production of anti-Sophy β-glucan IgG antibody in the blood of adult donors and neonates remains poorly understood at the present time; however, our data strongly suggest that innate as well as acquired immunity is established by anti-β-glucan antibody in living organisms for host defenses even from the time of birth.…”
Section: Immunological Actions Of Sophy β-Glucancontrasting
confidence: 53%
“…4). Although detection of an anti-β-glucan antibody in normal human and mouse sera has been reported previously (17,27), we found, for the first time, the presence of anti-Sophy β-glucan IgG antibody in serum samples prepared from the umbilical cord blood of neonates. The mechanism(s) of production of anti-Sophy β-glucan IgG antibody in the blood of adult donors and neonates remains poorly understood at the present time; however, our data strongly suggest that innate as well as acquired immunity is established by anti-β-glucan antibody in living organisms for host defenses even from the time of birth.…”
Section: Immunological Actions Of Sophy β-Glucancontrasting
confidence: 53%
“…Reactivity of AP-FBG to human -globulin preparation Since we had previously found antibodies against -D-glucan in human sera, 16) we first examined the reactivity of AP-FBG to polyglobin N. As shown in Fig. 1A, we found that AP-FBG exhibited high reactivity to antibodies in the human sera; this reactivity was stronger than that of GRN but weaker than that of CSBG.…”
Section: Resultsmentioning
confidence: 88%
“…13,14) Furthermore, although -glucans have long been considered to exhibit weak antigenicity, we reported that not only innate immune responses but also acquired immune responses, such as the production of antibodies against -glucans, are involved in the immunostimulatory effects of -glucans. 15,16) Very recently, we found that a unique type of -D-glucan obtained from the polymorphic fungus Aureobasidium pullulans (this -Dglucan is termed as AP-FBG) reacted to the antibodies in human sera; this -D-glucan has a mixed structure comprising a 1,3--D-glucan backbone with single 1,6--D-glucopyranosyl-branching units at every 2 nd residue as the major structure and a 1,3--D-glucan backbone with single 1,6--D-glucopyranosyl-branching units at every 3 rd residue as the minor structure (the ratio of the major and minor units was approximately 7:3). 17) The reactivity of AP-FBG was stronger than that of -Dglucan obtained from Grifola frondosa (GRN), which comprises a 1,3--D-glucan backbone with single 1,6--D-glucopyranosyl-branching units at every 3 rd residue, 18,19) while it was weaker than that of -glucan from Candida albicans (CSBG), which comprises a 1,3--Dglucan backbone with long 1,6--D-glucopyranosylbranching units.…”
Section: Involvement Of Branched Units At Position 6 In the Reactivitmentioning
confidence: 99%
“…One possible interpretation is that this patient was infected by C. famata or a close species that immunoreacts with the rabbit antibodies. On the other hand, the immune response (1,15,29). In conclusion, the clinician should consider the results from different tests on a case-by-case basis to determine the existence of infection.…”
Section: Discussionmentioning
confidence: 99%